Reading. Grade 3 connecting school and home - Mattenklodt, Kathy; Bonfield, Carol; Davis, Cindy; Larsen, Jo; Moore, Jo Ellen (Monterey, CA Evan-Moor Corp, 2005)
Provides at-home practice that helps to boost students' reading skills through engaging stories and activities that support Common Core State Standards. Activities provide practice of reading literature and informational text, and covers the essential components of reading instruction : comprehension, vocabulary, fluency, and phonics / structural analysis. Other literacy topics include grammar and writing
English Language
1
Keywords: Reading (Elementary); Reading comprehension